DEVELOPMENT OF INDUSTRIAL INVESTMENT IN IRAQ RELATED TO ECONOMIC GROWTH - AL-Chaabawi , Mohammed N. (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Economic growth, in Iraq, as in any other developing country, is a target which is constantly aimed at. industrial investment is an important instrument which has been used by Iraqi Governments during the last two decades in order to try and achieve economic growth. Iraq as a country is in need of research into the many different aspects of its urban and regional structure. The effects of industrial investment have not been studied in a careful way, especially the effects of investment on economic growth. So the aim of the current research was to identifying the impact of industrial investment on economic growth in Iraq. Data was collected from Central Bank of Iraq. The current study included, the impact of industrial investment as an independent variable on the Iraqi economic growth described by dependent variables (Foreign direct investment, manufacturing, value added current US, GDP growth annual %).The applied side focuses on three sections, where the first section focused on the mathematical description of the models under study. The second section dealt with the test of some standard problems suffered by the studied standard model. while the third section focused on estimating the models under study in the style of autoregressive distributed lag (ARDL). The findings of research based on estimation of the regression model using ARDL showed that the industrial investment has a positive and statistically significant effect on Iraqi economic growth.